Autoantibodies directed against apolipoprotein A-1 as a potential contributor to non-alcoholic fatty liver disease. (14th October 2021) - Pagano, S; Alfaiate, D; Juillard, C; Frias, M; Magenta, A; Martino, F; Sciaqua, A; Succurro, E; Burger, F; Brandt, K J; Andreozzi, F; Mach, F; et al.
Abstract: Background: Non-Alcoholic Fatty Liver Disease (NAFLD) represents an increasing cause of liver disease worldwide. Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in these patients. Although NAFLD pathophysiology is not fully understood alterations in fat metabolism seem to play a role. Autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) are a novel cardiovascular risk factor to which have been recently attributed a metabolic role in addition to a well-established macrophage-mediated inflammatory effect and have a function as a disruptor of the cholesterol pathway. Purpose: This study aims at evaluating a possible role of anti-apoA-1 IgG in NAFLD. Methods: Serum from 137 NAFLD patients were tested for anti-apoA-1 IgG prevalence. In vitro, SREBP1, SREBP2 expressions were assessed in the human hepatic cell line HepaRG by western blot analysis and bodipy staining was used to evaluate the lipid droplet content. Mescoscale technology platform was used to measure TNF-α, IL-6 and IL-8 cytokines/chemokines in HepaRG supernatants. Oil Red O staining was used to detect lipid accumulation in liver sections from ApoE−/− mice. Results: Elevated anti-apoA-1 IgG seropositivity was found in patients with NAFLD (46%). In vitro, anti-apoA-1 IgG and not control IgG induced lipid accumulation in hepatic cells (5.9 vs 2.5, P=0.0008) and this lipid overload was associated with a high SREBP1 but not SREBP2 expression. Furthermore, anti-apoA-1 IgG and not control antibodies caused a significant large increase of the proinflammatory cytokines IL-6 (680 vs. 163 pg/mL, P=0.03) and TNF-α (391 vs 266 pg/mL, P=0.04) as well as of the chemokine IL-8 (174.1 vs. 72.6 ng/mL, P=0.03) detected in the hepatic cell supernatants. In vivo, anti-apoA-1 IgG and not control IgG also induced higher lipid accumulation in the livers of ApoE−/− mice (1.23 vs 0.53, P=0.03). Conclusion: Anti-apoA-1 IgG are frequent in NAFLD, cause a strong inflammatory response and promote lipid accumulation through SREBP1 activation in human hepatic cells. We hypothesize that anti-apoA1 IgG may be a potential contributor in the development of NAFLD. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Geneva University Hospital